Influence of neuropathic pain on nicotinic acetylcholine receptor plasticity and behavioral responses to nicotine in rats. Issue 11 (November 2018) - Brunori, Gloria; Schoch, Jennifer; Mercatelli, Daniela; Ozawa, Akihiko; Toll, Lawrence; Cippitelli, Andrea
Abstract : Abstract: Tobacco smoking is particularly evident in individuals experiencing chronic pain. This complex relationship is poorly understood at both molecular and behavioral levels. Here, we describe experiments aimed at understanding whether a chronic pain state induces neuroadaptations into the brain or peripheral nerves that involve nicotinic acetylcholine receptors (nAChRs) and whether these neuroadaptations directly lead to increased vulnerability to nicotine addiction or to the development of coping strategies to relieve pain symptoms. We found that ligation of the rat L5 spinal nerve led to a dramatic downregulation in the mRNA expression levels of all nAChR subunits examined in dorsal root ganglia and a time-dependent downregulation of discrete subunits, particularly in the cingulate cortex and the amygdala. Spinal nerve ligation and sham-operated rats showed minor or no changes in patterns of acquisition and motivation for nicotine taking. Spinal nerve ligation rats also showed similar vulnerability to nicotine seeking as sham animals when reinstatement was induced by nicotine-associated cues, but failed to reinstate lever pressing when relapse was induced by nicotine priming. Spinal nerve ligation and sham rats were equally sensitive to nicotine-induced anxiety-like behavior and antinociception; however, nicotine produced a potent and long-lasting antiallodynic effect in spinal nerve ligation rats. These results demonstrate that chronic pain leads to plasticity of nAChRs that do not directly facilitate nicotine addictive behaviors. Instead, nicotine potently decreases allodynia, an effect that could lead to increased nicotine consumption in chronic pain subjects. Abstract : Supplemental Digital Content is Available in the Text.Tobacco smoking is prevalent in individuals experiencing chronic pain. This may be due to potent and long-lasting antiallodynic actions of nicotine in chronic pain subjects.